2015
DOI: 10.1038/onc.2015.129
|View full text |Cite|
|
Sign up to set email alerts
|

Lysine-specific demethylase 1 promotes the stemness and chemoresistance of Lgr5+ liver cancer initiating cells by suppressing negative regulators of β-catenin signaling

Abstract: Cancer initiating cells (CICs) are responsible for the unrestrained cell growth and chemoresistance of malignant tumors. Histone demethylation has been shown to be crucial for self-renewal/differentiation of stem cells, but it remains elusive whether lysine-specific demethylase 1 (LSD1) regulates the stemness properties of CICs. Here we report that the abundant expression of leucine-rich repeat-containing G-protein-coupled receptor 5 (Lgr5) is associated with the progression of hepatocellular carcinoma (HCC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 53 publications
4
110
0
Order By: Relevance
“…Consistent with Ru's finding in breast cancer [26], miR-203 can significantly reduce the potential for chemotherapy resistance. It is well known that EMT and tumor stemness signals participate in chemotherapy resistance [2729] We confirmed that miR-203 suppressed cell migration, invasion, tumor stemness, and DDP resistance by blocking EMT and stemness signal factors. This included downregulation of ZEB2, N-cadherin, BMI1, c-MYC, and NANOG, while inducing E-cadherin.…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with Ru's finding in breast cancer [26], miR-203 can significantly reduce the potential for chemotherapy resistance. It is well known that EMT and tumor stemness signals participate in chemotherapy resistance [2729] We confirmed that miR-203 suppressed cell migration, invasion, tumor stemness, and DDP resistance by blocking EMT and stemness signal factors. This included downregulation of ZEB2, N-cadherin, BMI1, c-MYC, and NANOG, while inducing E-cadherin.…”
Section: Discussionsupporting
confidence: 75%
“…LGR5 was shown to increase drug resistance, and in colon primary tumors, LGR5-high expression correlated with chemoresistance and lower disease-free and overall survival (16,17,20,23,42,43). Thus, an LGR5-targeting ADC may not only effectively treat gastrointestinal tumors, but also function to eliminate CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…CSCs can fuel tumor growth, confer resistance to standard chemotherapy and radiation, and are likely to contribute to recurrent disease (21). Correspondingly, high LGR5 expression in gastrointestinal tumors of different tissue types correlates with higher incidence of metastasis, drug resistance, and poor patient survival (16,(22)(23)(24). Thus, LGR5 may serve as an effective therapeutic target for the treatment of gastrointestinal cancers and CSC-based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al (117) used the lysine-specific demethylase 1A/prickle planar cell polarity protein 1/adenomatous polyposis coli/β-catenin signal axis as a novel molecular circuit to regulate the hepatocyte properties and chemoresistance of Lgr5 + LCSCs in liver, and the results confirmed that this signal axis may be used as a target for chemotherapy sensitization of liver cancer.…”
Section: Other Lcsc Targets and Their Applications In Tumor Therapymentioning
confidence: 59%